Relationship Among Family, Peer Networks, and Bulimic Symptomatology in College Women - Pauls, Brian Scott; Daniels, Thomas (Canadian Journal of Counselling and Psychotherapy, 2007)
This study tested the explanatory power of a sociocultural model in predicting bulimic symptomatology. Specifically, the family and peer systems of a sample of 141 college women were assessed using a variety of measures. The results revealed that high scores on the Bulimia Test were negatively correlated with scores on the cohesion subscale of the Family Adaptability and Cohesion Evaluation Scale. It was also found that the prevalence of bulimic symptomatology within a woman's peer system significantly predicted bulimic symptomatology in subjects. Pressures to diet from family and friends were also found to be associated with higher rates of bulimic symptomatology in these subjects. However, experiences of general problems in the peer systems of these subjects did not significantly predict bulimic symptomatology. Implications of this research are discussed.